Mothers prefer a hybrid model of postpartum care: a pilot mixed method study - Aminath Shiwaza Moosa; Zhimin Poon; Lindy Ai Keng Koh; Dhana Letchimy Kagradaimdoo; Yaesol Park; Yuhan Yang; Suliha Bivi; Ding Xuan Ng; Eileen Koh Yi Ling; Ngiap Chuan Tan (BMC, 2024)
Abstract Background Telehealth, including video consultation (VC), has become prevalent during the COVID-19 pandemic. However, the experience and concern of women using VC for postpartum care has yet to be adequately studied but is crucial for their adoption. The study aimed to assess the experience and attitude of postpartum mothers (PPM) towards using VC as a novel model of care delivery and the factors that could potentially affect their adoption. Method Data were gathered from PPM participating in VC using Zoom platform for postpartum care using mixed method. In-depth interviews (IDI) of twenty-five PPM were audio-recorded, transcribed verbatim and audited for accuracy. Thematic analysis was conducted to identify themes relating to perceived threat, usefulness, ease of use, and attitudes toward using VC in postpartum care. The themes are reported based on the "Health Information Technology Acceptance Model" framework. Preliminary quantitative data on the acceptability of VC were collected using structured surveys. Results PPMs valued convenience, accessibility, and personalised care VC offered to address their immediate postpartum concerns. They perceived VC as suitable for seeking medical opinions, improving confidence in parent crafting, and providing better care access. They recognised the lack of physical examination as a major limitation in VC and proposed a hybrid postpartum care model, combining VC and in-person consultation to cater to individual needs and preferences. PPMs alluded to trust in the care providers, flexibility in VC appointment timings and enhanced interface of remote platforms as enablers for VC adoption. Preliminary quantitative data shows that PPMs found VC saved time (100%), energy (98%), and money (90%) and was appropriate (94%), easy to use (96%), acceptable (96%) for postpartum care. Conclusion PPMs favoured combining VC and in-person consultation to mitigate their concerns and personalise their care needs.